Kelebihan Penduduk dan Konsumsi Berlebihan dalam Kasus Krisis Air Dunia - Ainun Jariah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
Amount of earthling in this time reach 6,6 billion growth level 76 million per year. According to United Nation amount of resident of earth will increase counted 2,6 billion in 2050. Care problem of excess of resident early when natural resources and environment star to destroy. Beside height growth of resident amount, pattern consume abundant human being result earth natural resources pressure mount also. This matter because of amount of higher resident as whole compared to ability of earth fulfill requirement of consumption resident of earth so that growth of high resident and also consumption which is abundant to be considered to be root problems of environment, among others irrigate crisis world. Irrigate crisis happened because of unconscious of human being will total up limited water and also increasing it is amount of human being owning is same requirement to water. Islam is one of the big religion in the world has important role in solving environment problem, that is with studying about ethical respon of Islam to clean water and proprietary rights irrigate as natural resource wich provide by nature. Inequal access clean water because of lack of awareness of human being will total up available under the sun water.